Cultural adaptation and reliability of the instrument "Five-part questionnaire on hypermobility" to the Peruvian context - Aranda-Sánchez, Melissa (2023)
Introduction For the diagnosis of joint hypermobility, the Beighton test is commonly used; this requires a professional for the physical examination. The "Five-part questionnaire on hypermobility" is a self-administered tool that allows early identification of joint hypermobility. Objective To carry out the cultural adaptation and test-retest reliability of the "Five-part questionnaire on hypermobility" to the Peruvian context through translation into spanish, linguistic adaptation, and verification of test-retest reliability in students from 13 to 17 years of age and teachers/ad-ministrators from 24 to 60 years of age. Methods A translation and back-translation were performed with two translators and two back-translators, followed by a linguistic adaptation with ten experts. Once the adapted version of the questionnaire was obtained, a comprehensibility analysis was carried out with 50 subjects. Finally, test-retest reliability was estimated in two groups: adolescents aged 13 to 17 and adults aged 24 to 60. Results The translated version of the questionnaire was obtained and underwent a linguistic adaptation process in which ten experts performed a concordance analysis (Aiken's V coefficient = 1), and a comprehensibility analysis with a scale of zero to ten obtained an average of ten points. Subsequently, this version was back-translated and checked against the original. In the reliability analysis, the results of the test-retest application found high reliability between the total score of both applications for both the group of 65 adults (Kappa 0.795; 95% CI: 0.777 to 0.819) and the group of 71 adolescents (Kappa 0.946; 95% CI: 0.908 to 0.982). Conclusions The translated instrument "Five-part questionnaire (5pq) on hypermobility" was adapted to the Peruvian cultural context, and high reliability was found for the study groups 13 to 17 years and 24 to 60 years. Concurrent validation is recommended to consider its application in clinical and research settings.